Feminist Policymaking in Chile - Haas, Liesl (Book collections on Project MUSE., 2010)
"Investigates the efforts of feminists in Chile to win policy reforms on a broad range of gender equity issues, from labor and marriage laws to educational opportunities to health and reproductive rights"--Provided by publisher